The epoxy resin system: function and role of curing agents - Aziz, Tariq; Haq, Fazal; Farid, Arshad; Cheng, Li; Chuah, Lai Fatt; Bokhari, Awais; Mubashir, Muhammad; Tang, Doris Ying Ying; Show, Pau Loke (Carbon Letters, 2024)
Curing agents are critical components of aqueous epoxy resin systems. Unfortunately, its uses and applications are restricted because of its low emulsifying yields. Epoxy resins are frequently used in electrical devices, castings, packaging, adhesive, corrosion resistance, and dip coating. In the presence of curing agents, epoxy resins become rigid and infusible. Eco-friendliness and mechanical functionality have emerged as vulcanization properties. Curing agents are used for surface modification, thermodynamic properties, functional approaches to therapeutic procedures, and recent advances in a variety of fields such as commercial and industrial levels. The curing agent has superior construction and mechanical properties when compared to the commercial one, which suggests that it has the potential for use as the architectural and industrial coatings. The thermal stability of cured products is good due to the presence of the imide group and the hydrogenated phenanthrene ring structure. Over the course of the projection period, it is anticipated that the global market for curing agents will continue to expand at a steady rate. The growth of the market is mainly driven by its expanding range in future applications such as adhesives, composites, construction, electrical, electronics, and wind energy. This review focused on the most recent advancements in curing techniques, emphasizing their thermal and mechanical properties. The review also presents a critical discussion of key aspects and bottleneck or research gap of the application of curing agents in the industrial areas.